Effect of Inspiratory Muscle Training on Anxiety and Depression in Patient with COPD that Received Pursed Lip Breathing - Yeanita; Rahmi Isma Asmara Putri (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: The presence of anxiety and depression in patients with Chronic Obstructive PulmonaryDisease (COPD) is often associated with greater disability, higher rates of exacerbations, increasedhospitalization and mortality. Many types of breathing exercises, such as Pursed Lips Breathing (PLB),Diaphragmatic Breathing (DBE), Respiratory Muscle Training (RMT), have been reported positivephysiological effects to reduces breathlessness, anxiety and depression in patients with COPD. Thisstudy aims to determine the effect in anxiety and depression after intervention of Inspiratory MuscleTraining (IMT) in COPD patients that received PLB.Methods: An experimental pre and post randomly study design, in August – September 2019. Controlgroup and experimental group each performed PLB exercises while the experimental group got additionalIMT. To evaluate anxiety and depression status, Hospital Anxiety and Depression Scale (HADS) wasused.Results: Twenty subjects with COPD were recruited, no significant differences of HADS score betweenboth groups. After 6 weeks of intervention, the HADS score in each group decreased significantly, withdelta of HADS score in experimental group was greater than the control group (p<0.05).Conclusion: Improvement of HADS scores after additional IMT was better than PLB only in COPDpatients.Keywords: chronic obstructive pulmonary disease; hospital anxiety and depression scale; inspiratorymuscle training; pursed lips breathing.